2022
DOI: 10.26442/00403660.2022.02.201367
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors for thromboembolic complications in patients with inflammatory bowel diseases

Abstract: Background. Inflammatory bowel diseases (IBD) are characterized by chronic immune inflammation of the mucous membrane and/or the thickness of the intestinal wall, and are also accompanied by disorders of the blood clotting system and the development of a hypercoagulation state. Aim. To identify the frequency of thromboembolic complications (TEC) in IBD patients and to determine the influence of acquired and inherited hypercoagulation factors that contribute to the development of TEС. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…The proposed mechanisms include the autoxidation of Hcy, formation of Hcy thiolactone as a toxic intermediate of Hcy, and inhibition of glutathione peroxidase activity [15]. Moreover, recent studies reported the connection between plasma Hcy levels and the risk of developing thromboembolic complications in IBD patients [16]. This is particularly important since hypercoagulable conditions in patients with IBD represent a significant cause of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanisms include the autoxidation of Hcy, formation of Hcy thiolactone as a toxic intermediate of Hcy, and inhibition of glutathione peroxidase activity [15]. Moreover, recent studies reported the connection between plasma Hcy levels and the risk of developing thromboembolic complications in IBD patients [16]. This is particularly important since hypercoagulable conditions in patients with IBD represent a significant cause of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…При участии ИЛ-8, в условиях хронического воспалительного процесса ИЛ-1,6 увеличивают высвобождение моноцитами тканевого фактора свертывания, подавляют процесс фибринолиза за счет ингибирования тромбомодулина. Активация протромбогенных факторов, сопровождается снижением количества ингибиторов свертывания -протеина С, протеина S и антитромбина [13].…”
unclassified